A simple prognostic score system predicts the prognosis of solitary large hepatocellular carcinoma following hepatectomy. Issue 31 (August 2016) - Shen, Jun-yi; Li, Chuan; Wen, Tian-fu; Yan, Lv-nan; Li, Bo; Wang, Wen-tao; Yang, Jia-yin; Xu, Ming-qing
Abstract : Abstract: Solitary large hepatocellular carcinomas (SLHCC) form a heterogeneous group of patients with different survival probabilities. The aim of our study was to develop a simple prognostic index for identifying prognostic subgroups of SLHCC patients. A retrospective analysis of clinical data from 268 patients with operable SLHCC was conducted to investigate prognostic factors and to construct a score system based on risk factors. A Cox proportional hazard regression analysis was used to evaluate the variables associated with prognosis. Survival analyses were performed using Kaplan–Meier survival curves. Three variables remained in the final multivariate model: platelet to lymphocyte ratio (PLR), microvascular invasion (MVI), and tumor size with hazard ratios equal to 1.004 (95% confidence interval: 1.001–1.006), 1.092 (1.044–1.142), and 2.233 (1.125–2.233), respectively. A score of 1 was assigned to each risk factor. Patient scores were determined based on these risk factors; thus, the scores ranged between 0 and 3. Ultimately, three categories (0, 1–2, 3) were defined. Patients with scores of 3 had a 5-year survival rate of 25.4%, whereas patients with a score of 0 had a 5-year survival rate of 52.1%. The prognosis significantly worsened as the score increased. Similar results were found among cirrhotic and noncirrhotic patients. Our simple prognostic index successfully predicts SLHCC survival.